2017
DOI: 10.1007/s10637-017-0526-0
|View full text |Cite
|
Sign up to set email alerts
|

Ganoderic acid, lanostanoid triterpene: a key player in apoptosis

Abstract: Cancer is a multifactorial disease, causing behavioral and metabolic alterations, leading to uncontrolled cell proliferation with collateral weakening of immune system. Crucial balance between cell proliferation and cell death determines the fate of a cell, which might progress towards survival or apoptosis. Apoptosis is a complex, programmed, and highly regulated process causing dramatic morphological and biochemical perturbations in the cellular machinery. Ganoderma lucidum is a basidiomycetes, polypore mush… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 57 publications
1
8
0
Order By: Relevance
“…Cyclin D1 is a downstream molecule of the PI3K/AKT pathway, and its overexpression has been linked to the development and progression of cancer . GA‐A has been reported to induce apoptosis in cancer cells through modulation of the PI3K/AKT pathway . In our study, the expression levels of phosphorylated AKT, mTOR, P70S6K, and cyclin D1 were significantly decreased after GA‐A treatment.…”
Section: Discussionsupporting
confidence: 52%
“…Cyclin D1 is a downstream molecule of the PI3K/AKT pathway, and its overexpression has been linked to the development and progression of cancer . GA‐A has been reported to induce apoptosis in cancer cells through modulation of the PI3K/AKT pathway . In our study, the expression levels of phosphorylated AKT, mTOR, P70S6K, and cyclin D1 were significantly decreased after GA‐A treatment.…”
Section: Discussionsupporting
confidence: 52%
“…Therefore, we concluded that GAA might alleviate hypoxia‐induced growth arrest and apoptosis through activating the PI3K/AKT pathway. Unlike the effects on NSCs, GAA suppresses proliferation and viability and induces apoptosis in cancer cells through either intracellular or extracellular pathway (Gill, Navgeet, Mehra, Kumar, & Kumar, ). The different downstream proteins and adapter molecules of GAA in stressed cells and cancer cells might explain the opposite effects of GAA on viability and apoptosis, which needs more experiments in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Two major active components are responsible: G. lucidum polysaccharides and G. lucidum triterpenoids (GTs) [ 15 ]. As one of the most abundant GTs, ganoderic acids (GAs) have anti-inflammatory, anti-oxidative stress, anti-tumor and anti-apoptotic effects [ 16 , 17 , 18 , 19 ]. It has been reported that Ganoderic Acid F, one component of GAs, can suppress LPS-induced the activation of NF-kB pathway and inhibit LPS-triggered iNOS expression and the production and secretion of relative inflammatory cytokines in mice [ 16 ].…”
Section: Introductionmentioning
confidence: 99%